Customer acceptance of internet banking services in Bangladesh: the case study of Bank Asia Limited - Muid, Noor-E-Alam Md (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.